Tinjauan Literatur: Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L) Terhadap Pemberian Pupuk Bioneensis dan Mikoriza Arbuskular - Pahruddin Siregar, Sahlan; Panggabean, Ellen Lumisar (Universitas Medan Area, 2025)
Peanuts are the fourth food commodity after rice, soybeans and corn. In terms of food crops, the existence of peanuts has a comparative advantage compared to other food crops. Excessive use of chemical fertilizers is a problem for soil fertility. Biofertilizers are one alternative in improving soil structure. Bioneensis is a biofertilizer made from a consortium of indigenous bacteria in oil palm roots (rhizome). Bioneensis contains N-binding microorganisms, P solvents and IAA producers which function as Plant Growth Promoting Bacteria (PGPR). Mycorrhiza is a fungus that is symbiotic in plant roots which is often used in agriculture, including helping to increase the presence of plant nutrients, increasing plant resistance to environmental stress, disease, and adverse conditions. This fungus is used as a biological agent to help increase plant growth during the vegetative and generative periods.